Small teaching K-8 : lighting your load with the science of learning - Sanders, Sarah Connell; Lang, James M. (Jossey-Bass, a Wiley Brand, 2023)
"While the original Small Teaching fills the gap in higher education literature between the primary research in cognitive theory and the classroom environment, this book applies the same foundational research to K-8 classrooms. Small Teaching is characterized by evocative storytelling, designed to convey compelling anecdotes across popular culture and individual schools in order to illustrate the issues, challenges, and opportunities presented in educators' classrooms every day. It offers simple interventions that can be integrated into pre-existing techniques as well as clear descriptions of how to do so. The book provides action items for energizing students that intentionally require minimal preparation and grading. The term "small teaching" refers to an approach that seeks to spark positive change in the classroom through small but powerful modifications to course design and teaching practices. A small teaching approach or activity may take one of three forms: brief classroom or online learning activities, one-time interventions in a course, or small modifications in course design or communication with students. Each chapter introduces a basic concept in cognitive research that has implications for classroom teaching, explains the rationale for offering it within a specific time period in a typical class, and then provides concrete examples of how this intervention has been used or could be used by faculty in a variety of disciplines"--